2005
DOI: 10.1345/aph.1e300
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Modified Dosing Weight for Heparin Therapy in a Morbidly Obese Patient

Abstract: Further investigation is necessary to determine the optimal DW for UFH in morbidly obese patients presenting with acute thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…A case report of a 54-year-old morbidly obese (182.4 kg, BMI 75 kg/m 2 ) woman treated with heparin for a highly probable pulmonary embolism described the use of a modified DW (average of IBW and ABW) of 120 kg to calculate the heparin bolus (80 units/kg [9600 units]) and initial infusion rate (18 units/kg/hr [2160 units/hr]). 17 A therapeutic aPTT (target range 70-115 sec; equivalent to a heparin concentration of 0.3-0.7 units/ml) was achieved in this patient within 10 hours with the initial infusion rate of 2160 units/hour. The heparin aPTT was maintained at the higher end (94.7-116.9 sec) of the target aPTT range (70-115 sec) for the duration of therapy (6 days).…”
Section: Reports From the Centers For Disease Control And Prevention mentioning
confidence: 72%
See 1 more Smart Citation
“…A case report of a 54-year-old morbidly obese (182.4 kg, BMI 75 kg/m 2 ) woman treated with heparin for a highly probable pulmonary embolism described the use of a modified DW (average of IBW and ABW) of 120 kg to calculate the heparin bolus (80 units/kg [9600 units]) and initial infusion rate (18 units/kg/hr [2160 units/hr]). 17 A therapeutic aPTT (target range 70-115 sec; equivalent to a heparin concentration of 0.3-0.7 units/ml) was achieved in this patient within 10 hours with the initial infusion rate of 2160 units/hour. The heparin aPTT was maintained at the higher end (94.7-116.9 sec) of the target aPTT range (70-115 sec) for the duration of therapy (6 days).…”
Section: Reports From the Centers For Disease Control And Prevention mentioning
confidence: 72%
“…A variety of case reports and retrospective studies were identified. [11][12][13][14][15][16][17][18] References of the articles were reviewed to identify additional literature. The variability in the weight evaluated-ABW versus dosing weight (DW)-and in the definition of obesity used limits the ability to draw a definitive recommendation on the best approach.…”
mentioning
confidence: 99%
“…Additionally, Riney et al have found that the required heparin dose per kilogram of body weight for high BMI patients was obviously lower than that for low BMI patients to reach similar APTT values (18). Therefore, the heparin loading doses could be administered according to ideal body weight, corrected weight, or dose of heparin per blood volume of the obese patients to avoid bleeding complications that was still lack of practical clinical researches (17). In conclusion, the results of our study have shown that a standardized dosing nomogram that uses the actual body weight to calculate the heparin doses may result in UFH overdose for patients with higher BMI compared to patients with lower BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple case reports have suggested the use of various modified or adjusted ''dosing weight'' (DW) for calculation of doses in obese patients (30)(31)(32). Delays varied from 10 to 48 hours to achieve a threshold aPTT.…”
Section: Obesitymentioning
confidence: 99%